Exposures associated with tuberculosis presentation and healthcare delays in South West England, 2015–2020 - Gemma Lyness; Neville Q. Verlander; Charles R. Beck (PLoS ONE, 2026)
Significant progress has been made in reducing the tuberculosis (TB) rate in England over the last decade. South West England has a low incidence of TB, but over a third of people with pulmonary TB (pTB) had a treatment delay of over four months in 2020, higher than the England average. This study aimed to identify the exposures associated with presentation and healthcare delays in receiving pTB treatment in the South West of England between 2015 and 2020. This retrospective cohort study included all confirmed persons with TB resident in South West England, receiving treatment between 2015 and 2020. Univariate and multivariable Cox proportional hazards ratios were produced for the outcome measures of presentation and healthcare delays for persons with pTB. Multivariable regression models were fitted using a forward, stepwise procedure. Sensitivity analyses excluded treatment delays over two years and the year 2020. Data were analysed using Stata 17. Between 2015 and 2020 there were 812 persons with pTB among South West residents. Median treatment delays were 35 days for presentation and 25 days for healthcare delay. Multivariable analysis identified that longer presentation delays were associated with being aged 35–50 or over 80 years old. Longer healthcare delays were associated with increasing age (hazard ratio [HR]: 0.99, 95% CI: 0.98–0.99), being employed (HR: 0.71, 95% CI: 0.52–0.97) and people currently or historically deprived of their liberty and accommodated by a prison (HR: 0.33, 95% CI: 0.20–0.54). Shorter healthcare delays were associated with sputum smear positivity (HR: 1.54, 95% CI: 1.16–2.06) and smoking (HR: 1.64, 95% CI: 1.22–2.22). Delays between symptom onset and TB treatment remain an important public health problem in the region. Factors have been identified that can be investigated to reduce presentation and healthcare delays. Detailed analyses were valuable in disaggregating key populations. Further mixed-methods research would be warranted to further understand these associations.